Absenteeism, Health and Work Activity of Older Employees in the Context of the Rising Retirement Age - Novak, Vesna (Sodobni pristopi v kadrovskem managementu in izobraževanju, 2026)
This paper addresses the issue of ageing populations, a key challenge for the sustainability of pension systems and public finances. In response, countries often raise the retirement age, which has both positive and negative effects. Poor health of older individuals is frequently mentioned as a negative consequence. Therefore, the paper focuses on changes in retirement conditions related to the health of older workers. We analyzed sick leave data across different age groups of employees in Slovenia and presented self-assessed health for both the general and working-age populations. Self-reported health declines with age, and absenteeism increases, indicating a need for adjustments in the work environment and other measures for older workers. Based on the reviewed literature and the negative consequences of raising the legal retirement age, we conclude that the decision to continue working after 65 should be based on voluntariness and individual abilities, not forced by neoliberal policies.